(untitled) - Laureano, M.; Pedro Ribeiro; Fernando Silva; José Dernando Mendes (Lecture Notes in Computer Science, 2022)
This book constitutes the refereed proceedings of the 7th International Conference and School of Network Science, NetSci-X 2022, held in Porto, Portugal, in February 2022. The 13 full papers were carefully reviewed and selected from 19 submissions. The papers deal with the study of network models in domains ranging from biology and physics to computer science, from financial markets to cultural integration, and from social media to infectious diseases.